2010
DOI: 10.1094/php-2010-0317-01-rv
|View full text |Cite
|
Sign up to set email alerts
|

Potato Zebra Chip Disease: A Phytopathological Tale

Abstract: Potato zebra chip (ZC) disease is a relative newcomer to the world of important potato diseases. First reported in Mexico in the 1990s, by 2004-2005 the disease was causing serious economic damage in parts of Texas. ZC is now widespread in the south-western and central United States, Mexico, Central America, and was recently reported in New Zealand. By 2006, there seemed to be an association between ZC and the potato psyllid (Bactericera cockerelli). The exact nature of the relationship, however, has only rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
89
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(90 citation statements)
references
References 23 publications
1
89
0
Order By: Relevance
“…A large number of tubers from stolbur-infected potato plants produced fried chips that were defective and unmarketable. However, these tubers did not exhibit characteristic symptoms of zebra chip disease, a newly emerging and destructive disease of potato in the Americas and New Zealand (Munyaneza et al 2007b;Munyaneza et al 2008a;Liefting et al 2008;Secor et al 2009;Crosslin et al 2010). Although above-ground plant symptoms of stolbur phytoplasma infection in potato resemble those caused by zebra chip, the tuber symptoms are different.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of tubers from stolbur-infected potato plants produced fried chips that were defective and unmarketable. However, these tubers did not exhibit characteristic symptoms of zebra chip disease, a newly emerging and destructive disease of potato in the Americas and New Zealand (Munyaneza et al 2007b;Munyaneza et al 2008a;Liefting et al 2008;Secor et al 2009;Crosslin et al 2010). Although above-ground plant symptoms of stolbur phytoplasma infection in potato resemble those caused by zebra chip, the tuber symptoms are different.…”
Section: Discussionmentioning
confidence: 99%
“…Ca. Liberibacter psyllaurous) (Crosslin et al 2010), is transmitted from infected to healthy plants by the psyllid vector, Bactericera cockerelli (Munyaneza et al 2007a, b). Tubers from infected plants exhibit characteristic brown discoloration of vascular tissue and contain high levels of glucose, fructose (reducing sugars) and free amino acids (Wallis et al 2012;Rashed et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…B. cockerelli has an extensive range of acceptable hosts, including species in 20 plant families, but solanaceous species (tomatoes, potatoes, nightshade) are preferred (Wallis 1955). Crosslin et al (2010) reported a spread of ZC across geographic regions by dispersing B. cockerelli which helped maintain the bacterium in these regions during the insect's overwintering period. Munyaneza et al (2011) reported yield losses due to B. cockerelli and ZC damage ranging from 43% to 93% in several commercial potato varieties under controlled field cage conditions in Texas and Washington State.…”
mentioning
confidence: 99%